Enhancing Geometric Fidelity of 3-Dimensional Electroanatomic Mapping During Open Chest Epicardial Radiofrequency Catheter Ablation - Gabriel E. Soto MD, PhD, MHCDS, FACC, FHRS; Joseph G. Gibbons RN (SAGE Publishing, 2019)
Although electroanatomic mapping techniques have been previously applied to open chest epicardial ablation procedures, such efforts have often been limited by significant geometric distortions introduced by the need to use nonstandard mapping patch placements and by intrathoracic conductance changes introduced by having the pericardial space exposed. In this article, we present a case of a patient with recurrent hemodynamically unstable ventricular tachycardia who underwent a successful open chest epicardial ablation procedure with electroanatomic mapping in which geometric distortions were minimized by judicious placement of mapping patches and the use of a saline bath within the pericardial space.